RESOURCE BASED VIEW DAN PEMBERDAYAAN - Kesi Widjajanti (Jurnal Ekonomi dan Bisnis, 2010)
Resource Based View is an important issue correlate to funding source preferences in welfareof the society. There are research gap about the limited study to focus anteceden empowermentprocess toward increase ability society.The concept needs to be clarified by empirical fact.Therefore, this research proposed â€œa research problemâ€: how define the process of improvinga society ability through developing human capital, empowerment process and subject ability.The research object is the society Sumber Rahayu Central Java. The method sampling usesthe non-probability method. The sample of this research includes 104 persons. Statisticalanalysis was used to analyse this data. Descriptive statistic used to describe specificationof the characteristics being investigated. The Structural Equation Modeling (SEM) of SmartPartial Least Square statistical software package was used in modeling and hypothesistesting. Result indicates resource potential changing into a source advantage. The implicationfrom this research contributed in relationship between human capital, empowerment processand society ability.Keyword: Resource, Empowerment, Human Capital, Society Ability